2017
DOI: 10.1108/ijrdm-12-2016-0240
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging shoplifting prevention with quality relationships

Abstract: Purpose The cost to supermarkets from shoplifting is a growing problem. Despite huge investments in formal security measures, supermarkets experience shrinkage and face heavy financial losses. Hence, this paper explores an alternative approach to shoplifting prevention. The purpose of this paper is to propose that quality relationships between a supermarket and its customers could be a viable strategy for shoplifting prevention. A conceptual model is presented at the end of this paper for encouraging shoplifti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…These types of initiatives, in turn, can positively influence and discourage antisocial and/or criminal acts aimed at these companies. This way of thinking is in line with the recommendation made by Potdar et al () for preventing employee theft. By implementing excellent relations with customers as well as the community, businesses can create goodwill, which acts as an additional and positive deterrent.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These types of initiatives, in turn, can positively influence and discourage antisocial and/or criminal acts aimed at these companies. This way of thinking is in line with the recommendation made by Potdar et al () for preventing employee theft. By implementing excellent relations with customers as well as the community, businesses can create goodwill, which acts as an additional and positive deterrent.…”
Section: Discussionsupporting
confidence: 84%
“…The National Retail Security Survey, which is conducted annually by the National Retail Federation trade group, found that the loss of inventory from stores due shoplifting and employee theft cost the US retail industry almost $50 billion in 2016, with the trade group estimating an average cost per shoplifting incident of $800 (Reilly, ). Potdar, Guthrie, and Gnoth () also indicate that supermarkets experience shrinkage and face substantial financial losses caused by shoplifting, despite investing in formal security measures. Therefore, traditional security measures alone are not sufficient to prevent shoplifting.…”
Section: Introductionmentioning
confidence: 99%
“…Patrus et al (2013) asserted that a socially responsible company creates organizational values and seeks to improve the social conditions of people affected by its actions. Likewise, retailers that participate in CSR activities can positively enhance the relationship between retailer and customer (Potdar, Guthrie & Gnoth, 2018). CSR has been studied from many different perspectives and in contexts such as the relationship between CSR and employees' perceptions (e.g.…”
Section: Csr and Crmmentioning
confidence: 99%
“…Cavazos-Arroyo et al, 2017) and consumers' shoplifting prevention behaviour (e.g. Potdar et al, 2018). However, TPB has not been used in the context of consumers' participation intention regarding CRM.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%
See 1 more Smart Citation